Ocena samostojnosti stanovalcev, obolelih z demenco, pri zadovoljevanju temeljnih življenjskih potreb v domovih starejših v Ljubljani - Kobentar, Radojka (Zdravniški vestnik, 2015)
Background: Obviously, a very high proportion of nursing home residents present with clinical signs of dementia, which affect the independence of the impaired individual. The purpose of the study is to determine the level of independence of the residents in performing basic life activities. Methods: The research included 233 residents of both genders with a clinical diagnosis of dementia, aged 65 years and over, who had resided in one of the four Ljubljana municipality nursing homes for at least one year prior to the begin of the study. The autonomy in carrying out 11 basic live activities was measured on a three-level scale and their cognitive skills by a quick test of cognitive abilities (KPSS). The data were processed by means of SPSS, ver. 13.0 and methods of descriptive statistics; chi-square test was used for the statistic argumentation of research questions. The level of statistical significance was calculated at p = 0.05. Results: The study population sample showed a high cognitive decline measured on the KPSS scale, as 50.2 % of subjects in mid-stage reached 24-11 points and 43.4 % of those in the late-stage reached 10-0 points on a 30-point scale. Only 6.4 % of the examined population in the early stage reached 29-25 points. The significant findings may thus indicate a high overall entire dependency on the implementation of all 11 life activities (59.7-74.2 %) on the three-level scale (1 being self-sufficient, 2 and 3 standing for partially dependent and entirely dependent, respectively). Conclusions: The examined nursing home residents in the sample, suffering from demen tia, show a high degree of dependency in performing basic life activities. The survey results so far present a starting point for the planning of programmes for increasing involvement of residents' involvement in psychosocial activities through practical exercises of self-sufficiency in the implementation of basic life activities.
Keywords: clinical mentors; gerontological knowledge; gerontološka znanja; klinični mentorji; nursing of older people; students; študentje; zdravstvena nega starostnika